Perspectives of patients with type 1 or insulin-treated type 2 diabetes on self-monitoring of blood glucose: a qualitative study - Hortensius Johanna; Kars Marijke C; Wierenga Willem S; Kleefstra Nanne; Bilo Henk JG; van der Bijl Jaap J (BMC, 2012)
Abstract Background Self-monitoring of blood glucose (SMBG), including self-regulation, is an important tool to achieve good glycemic control. However, many patients measure their glucose concentrations less often than is recommended. This study investigates patients' perspectives of SMBG and all relevant aspects influencing SMBG in patients with type 1 and insulin-treated type 2 diabetes. Methods In depth interviews were conducted with 13 patients with type 1 diabetes from an outpatient clinic and 15 patients with type 2 diabetes from general practices. All interviews were transcribed verbatim and analyzed using the Grounded Theory approach. Results A wide variety of SMBG was encountered. Perceptions, goals of SMBG and personal and contextual factors were identified, influencing the respondents' perspective of SMBG, and leading to this variety. Respondents experienced a discrepancy between their own and the professionals' perceptions and goals. Respondents' perception of SMBG ranged along a continuum from 'friend' to 'foe'. With respect to the goals, the respondents experienced tension between achieving good glycemic control and quality of life, and deliberately made their own choices. The performance of SMBG was tailored to their perceptions and personal goals. Personal and contextual factors such as hypo- or hyper (un)awareness, knowledge, and contact with professionals acted as either facilitating factors or as barriers to SMBG, depending on the respondents' perspective. A SMBG model was developed providing a representation of the factors and their interrelations. Respondents with type 1 diabetes seemed more resigned to their situation and SMBG was more integrated into their lives. Conclusions From the patients' perspective, professionals positively present SMBG as a 'friend' in order to achieve strict glycemic control. Whereas patients can also perceive SMBG as a 'foe'. They primarily seek a personal balance between achieving glycemic control and quality of life, leading them to deliberately make other choices regarding SMBG performance than was recommended. Gaining insight and discussing all factors affecting SMBG will help professionals and patients come to mutually agreed goals and to tailor the performance of SMBG to the individual patient. This should result in a more optimal use of SMBG, an improved quality of life, and improved clinical parameters.